2019
DOI: 10.3389/fcimb.2019.00021
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of 21-Plex PCR and API 20C AUX, MALDI-TOF MS, and rDNA Sequencing for a Wide Range of Clinically Isolated Yeast Species: Improved Identification by Combining 21-Plex PCR and API 20C AUX as an Alternative Strategy for Developing Countries

Abstract: Occurrence of non- Candida albicans Candida (NCAC) species that are associated with elevated MIC values and therapeutic failures are increasing. As a result, timely and accurate means of identification to the species level is becoming an essential part of diagnostic practices in clinical settings. In this study, 301 clinically isolated yeast strains recovered from various anatomical sites [Blood ( n = 145), other sites ( n = 156)] were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 39 publications
(65 reference statements)
0
18
0
Order By: Relevance
“…The majority of Fig. 2 The distribution of the yeast from VVC by years misidentified yeast isolates were among rare species (n = 45), and the majority (4/5) of Pichia kudriavzevii strains were misidentified [25]. The closely related Candida complex was identified from vaginal samples by using molecular methods [8,[16][17][18][19]26].…”
Section: Strain Identification and Distributionmentioning
confidence: 99%
“…The majority of Fig. 2 The distribution of the yeast from VVC by years misidentified yeast isolates were among rare species (n = 45), and the majority (4/5) of Pichia kudriavzevii strains were misidentified [25]. The closely related Candida complex was identified from vaginal samples by using molecular methods [8,[16][17][18][19]26].…”
Section: Strain Identification and Distributionmentioning
confidence: 99%
“…The 21-plex PCR showed a higher degree of accuracy for the yeast species included in this study compared with the Vitek 2 system. A previous study found a higher degree of accuracy when 21-plex PCR, as the first line identification tool, was used in combination with API 20C AUX for isolates that were not identified by 21-plex PCR [ 17 ]. 21-plex PCR showed superiority over the Vitek 2 system and the vast majority of rare yeasts and even a few isolates of the main Candida species were not correctly identified by the Vitek 2 system.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, accurate and rapid identification tools, such as matrix-assisted laser desorption ionization time-of-flight and Sanger sequencing, which are common in Western countries, are largely unaffordable for most clinical laboratories of developing countries, and most of the identifications are performed by inaccurate and expensive phenotypic tools [ 123 ]. To help overcome this issue, a comprehensive multiplex PCR was introduced [ 230 ], which can identify the most clinically important yeast species causing infection in humans and numerous studies afterward showed its reproducibility in various epidemiological studies [ 92 , 231 , 232 ]. Although such techniques are far from ideal, their application can significantly shorten the turnaround time and improve the species identification accuracy.…”
Section: Optimizing Therapy By Species Identificationmentioning
confidence: 99%